81.3k views
5 votes
Use the equation equation y = -3x + 2 to find the missing value.Given the output = -4

User Jcoffland
by
5.7k points

1 Answer

4 votes

Answer:

x=2

Step-by-step explanation:

We need to find the value of x when y is equal to -4

So, if we replace y by -4 on the initial equation, we get:

y = -3x + 2

-4 = -3x + 2

So, subtracting 2 on both sides of the equation:

-4 - 2 = -3x + 2 - 2

-6 = -3x

Dividing by -3, we get:


\begin{gathered} (-6)/(-3)=(-3x)/(-3) \\ 2=x \end{gathered}

Therefore, the missing value is x = 2

User Nick Sanders
by
5.7k points